S-band electron linac with beam energy of 30…100 MeV - Antipov, K.I.; Ayzatsky, M.I.; Akchurin, Yu.I.; Gurin, V.A.; Boriskin, V.N.; Beloglasov, V.I.; Biller, E.Z.; Demidov, N.V.; Dovbnya, A.N.; Dronov, R.N.; Khodak, I.V.; Kosoy, A.I.; et al. (Вопросы атомной науки и техники, 2004)
The S-band electron linac has been designed at NSC KIPT to cover an energy range from 30 to 100 MeV. The linac consists of the injector based on evanescent oscillations and the two four-meter long piecewise homogeneous accelerating sections. Each section is supplied with RF power from the KIU-12AM klystron. Variation of mean energy of the beam over a wide range is produced by placing bunches out of the wave crest in the second accelerating section. The report presents layout of the linac as well as simulation results of self-consistent particle dynamics in the linac and its present status.